Clinical case of heart transplantation in the conditions of «the recipient-to-donor» transportation - B.M. Todurov; O.O. Samchuk; G.I. Kovtun; A.O. Shpachuk; M.V. Goncharenko; I.M. Kuzmich; O.M. Druzhina; O.A. Loskutov; O.I. Kvasha; S.M. Sudakevich; A.Yu. Melnik; Yu.I. Golik; et al. (Кардіохірургія та інтервенційна кардіологія)
The main factor limiting the number of heart transplants in Ukraine is the small number of potential donors. In cases when the delivery time of the donor organ is more than 4 hours, the risks of the donor organ ischemic injury are multiplied. Transportation of the recipient to the location of the potential donor in such cases is a forced measure, as it increases the risk of adverse cardiovascular events in the recipient during transportation. Providing medical care to a recipient in such circumstances may be difficult. However, these measures are fully justified by the reduced risk of postoperative complications associated with the time of graft ischemia. The article describes a case of heart transplantation in the conditions of transporting the recipient to the donor. Heart transplantation was performed in a patient with NYHA functional class IV heart failure, refractory to conservative therapy. The postoperative period was uneventful. The time of cardiopulmonary bypass was 90 minutes, the total ischemia time was 180 minutes. On the 3rd day, the patient was transported to the specialized centre to continue treatment and rehabilitation. On the 21st day the patient was discharged in satisfactory condition for outpatient treatment.